Sentential Negation in the Imilike Dialect of Igbo (2015)
In spite of the fact that negation is a universal principle of human language, the process of negation and negative markers tends to be distinct across languages and dialects. This descriptive study therefore examines the process of achieving sentential negation in the Imilike dialect of the Igbo language. Its specific objectives are to identifying negative markers and negative polarity items; and show how negators interact with other functors in the dialect. Data for the study were collected from native speakers through oral interview and observation. Analysis is based on the verb forms identified in the dialect in relation to their affirmative counterparts. The results show that negative markers in the dialect are - ga/-g~ and -le/-If! which are suffixes. The former is used in the indicative, progressive and future tense/aspectual forms, while the latter is employed in imperative constructions. Tense/aspect markers such as the past, the perfective, the progressive and the future have negative forms which cooccur with the main negator in negative constructions. The study shows the rich inflectional and phonological properties of the dialect such as affix sequencing and vowel harmony. The study concludes that the process of negation and negative markers in Imilike Igbo is noticeably distinct from those of standard lgbo.